Aging, proteotoxicity, mitochondria, glycation, NAD+ and carnosine: possible inter-relationships and resolution of the oxygen paradox - Hipkiss, Alan R. (Frontiers in Aging Neuroscience, 2010)
It is suggested that NAD+ availability strongly affects cellular aging and organism lifespan: low NAD+ availability increases intracellular levels of glycolytic triose phosphates (glyceraldehyde-3-phosphate and dihydroxyacetone-phosphate) which, if not further metabolized, decompose spontaneously into methylglyoxal (MG), a glycating agent and source of protein and mitochondrial dysfunction and reactive oxygen species (ROS). MG-damaged proteins and other aberrant polypeptides can induce ROS generation, promote mitochondrial dysfunction and inhibit proteasomal activity. Upregulation of mitogenesis and mitochondrial activity by increased aerobic exercise, or dietary manipulation, helps to maintain NAD+ availability and thereby decreases MG-induced proteotoxicity. These proposals can explain the apparent paradox whereby aging is seemingly caused by increased ROS-mediated macromolecular damage but is ameliorated by increased aerobic activity. It is also suggested that increasing mitochondrial activity decreases ROS generation, while excess numbers of inactive mitochondria are deleterious due to increased ROS generation. The muscle- and brain-associated dipeptide, carnosine, is an intracellular buffer which can delay senescence in cultured human fibroblasts and delay aging in senescence-accelerated mice. Carnosine’s ability to react with MG and possibly other deleterious carbonyl compounds, and scavenge various ROS, may account for its protective ability towards ischemia and ageing.